Comparative Analysis of Cryotherapy Modalities Using Muscle Tissue Temperature Measurement: Cold Pack, Cold Compression, and Hyperbaric Gaseous Cryotherapy - Jinyeob Baek; Jaeeon Cheon; Hyeonseo Lim; Yong Yu; Suyoung Heo (Veterinary Sciences)
Cryotherapy is widely used in veterinary medicine to manage pain and swelling, yet optimal methods for specific tissue depths remain unclear. Cryotherapy modalities, including cold packs (CPs), cold compression (CC), and hyperbaric gaseous cryotherapy (HGC), were applied to nine beagle dogs under general anaesthesia. A custom 3D-printed guide facilitated consistent and accurate measurements of tissue temperatures at depths of 1 and 3 cm. After a 20 min application, all modalities significantly reduced the muscular tissue temperatures at both measured depths. HGC exhibited the most effective rapid temperature reduction, whereas CC displayed the most extended sustained cooling effect. In comparison, CPs showed a lower temperature reduction. The effectiveness of cryotherapy varies with tissue depth, and selecting the appropriate method can improve therapeutic outcome.